NiFe2O4/ZnO-coated Poly(L-Lactide) nanofibrous scaffold enhances osteogenic differentiation of human mesenchymal stem cells - Shariati, Shiva; Seyedjafari, Ehsan; Mahdavi, Fatemeh Sadat; Maali, Amirhosein; Ferdosi-Shahandashti, Elaheh (Frontiers in Bioengineering and Biotechnology, 2022)
Background: A combination of bioceramics and polymeric materials has attracted the research community's interest in bone tissue engineering. This composite is essential to support cell attachment, proliferation and osteogenesis differentiation, which are vital as a classic strategy in bone tissue engineering. In this study, NiFe2O4/ZnO-coated poly L-Lactide (PLLA) was employed as a scaffold to evaluate the osteogenic differentiation capability of human Adipose tissue-derived Mesenchymal Stem Cells (hAMSCs). Material and methods: The electrospun PLLA nanofibers were fabricated, coated with nanocomposites(NiFe2O4/ZnO) and evaluated by the water contact angle, tensile test, ATR-FTIR and Scanning Electron Microscopy (SEM). Then, the osteogenic differentiation potential of hAMSC was evaluated in vitro using NiFe2O4/ZnO-coated PLLA compared to tissue culture plastic (TCP) and a simple scaffold (PLLA). Results: The adhesion, proliferation and differentiation of AMSC were supported by the mechanical and biological properties of the NiFe2O4/ZnO-coated PLLA scaffold, according to SEM and DAPI staining patterns. During bone differentiation, Alkaline phosphatase activity, biomineralization, calcium content and osteogenic mRNA expression (Alkaline phosphatase, Osteonectin, Osteocalcin, Collagen type I and Runx2) were considerably greater on NiFe2O4/ZnO-coated PLLA scaffold than on PLLA scaffold and TCP. Conclusion: According to our findings, when h-AMSCs become in proper relation with NiFe2O4/ZnO-coated PLLA, biomimetic features are formed that can be used to stimulate and accelerate the osteogenic differentiation of hAMSCs for bone regenerative medicine.